Challenges and opportunities for entrepreneurship Post Pandemic five-year economic crisis – a study of JHANSI District of Uttar Pradesh - Sahu, Pratibha; Tiwari, Era; Nigam, Devesh; Dixit, Sajal (Revista Review Index Journal of Multidisciplinary, 2026)
Background: This study examines the impact of the COVID-19 crisis on enterprises in Jhansi district of Uttar Pradesh, India. Objective: Challenges and opportunities faced by entrepreneurs during the pandemic were analyzed. SWOC analysis for entrepreneurial activities during the pandemic was also conducted. Best practices adopted by entrepreneurs to minimize the impact of shocks generated by the COVID-19 economic crisis. Methodology: The descriptive and exploratory research design has been used in the study. A sampling survey method and case study approach were used. Samples for data collection were selected through snowball sampling through google form online. Ninety-four respondents participated through an open sampling technique and were divided into two equal sub-samples. The first sub-sample consisted of individuals who were employed, and the second included job seekers for in-depth examination. Result: The findings indicate that most entrepreneurs suffered significantly during the crisis. Many entrepreneurs started doing business through e-commerce. Several faced lower production and unavailability of products for sale after the lockdown was lifted. SWOC analysis results showed: strengths—less borrowings, capital incentives; weaknesses—interruptions in the supply chain; opportunities—electronic activities, work from home, greater business flexibility, and government schemes; challenges—closing the economy, economic downturn, and declining purchasing power.